2014
DOI: 10.1371/journal.pone.0089723
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of HIV among Chinese Tuberculosis Patients by Provider-Initiated HIV Testing and Counselling (PITC): A Multisite Study in South Central of China

Abstract: BackgroundTuberculosis (TB) and HIV are two worldwide public health concerns. Co-infection of these two diseases has been considered to be a major obstacle for the global efforts in reaching the goals for the prevention of HIV and TB.MethodA comprehensive cross-sectional study was conducted to recruit TB patients in three provinces (Guangxi, Henan and Sichuan) of China between April 1 and September 30, 2010.ResultsA total of 1,032 consenting TB patients attended this survey during the study period. Among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…On the other hand, previous studies have shown that patients with TB that had a history of drug use compared to non-addicts people were more likely prone to acquire AIDS (15,16). Multivariate regression analysis in this study revealed that drug abuse can be an important risk factor for incidence of TB in HIV positive patients.…”
Section: Discussioncontrasting
confidence: 45%
“…On the other hand, previous studies have shown that patients with TB that had a history of drug use compared to non-addicts people were more likely prone to acquire AIDS (15,16). Multivariate regression analysis in this study revealed that drug abuse can be an important risk factor for incidence of TB in HIV positive patients.…”
Section: Discussioncontrasting
confidence: 45%
“…This might be the main reason for higher HIV infection among alcohol drinking patients. It was in agreement with one study carried out in south central china (Xu et al, 2014). TB patients previously diseased by the same health problem were more likely to be infected with HIV in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Prevalence of HIV infection among smear-positive pulmonary TB was 6.8 % (15/220). It was in agreement with the rate estimated by Datiko and co investigators in rural area of Gamo Goffa zone and the national estimate of TB-HIV co-infection in Ethiopia, Angola (Datiko et al, 2008 andWHO, 2013) and also in south central China (Xu et al, 2014), Gambia (Hill et al, 2006), and in some districts of India (Seth, 2011). However, it was in contrast to most studies carried out in Ethiopia (Alemie andGebreselassie, 2014 andTadesse andTadesse, 2013), South Africa [Louwajie andAyo-Yosuf , 2013 andJohn et al, 2007), Tanzania (Macpherson et al, 2011), Brazil (Carvalho et al, 2008 Nigeria (Erhabor et al, 2010, Olugbue and Onuoha, 2012and Pennap et al, 2010, in eastern and western European countries and European economic areas (Pinpin et al, 2011) and Kenya (Nymagoba et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…8 Deaths among people with both HIV and tuberculosis are classified as deaths from HIV in ICD-10. Due to a low percentage of HIV-positive people in the study population (0.28–3.30%), 9 , 10 all participants were assumed to be HIV-negative. The case-fatality rate is defined as the risk of death from tuberculosis among people diagnosed with active tuberculosis.…”
Section: Methodsmentioning
confidence: 99%